2004
DOI: 10.1086/386324
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea purpurea for Prevention of Experimental Rhinovirus Colds

Abstract: A randomized, double-blind, placebo-controlled clinical trial was conducted to evaluate the ability of Echinacea purpurea to prevent infection with rhinovirus type 39 (RV-39). Forty-eight previously healthy adults received echinacea or placebo, 2.5 mL 3 times per day, for 7 days before and 7 days after intranasal inoculation with RV-39. Symptoms were assessed to evaluate clinical illness. Viral culture and serologic studies were performed to evaluate the presence of rhinovirus infection. A total of 92% of echi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 19 publications
0
74
0
Order By: Relevance
“…Thus, the results indicate that, in this study, echinacea was no more effective than placebo in preventing rhinovirus infection. However, it is possible that the study did not have sufficient statistical power to detect a difference between the two groups (Sperber et al 2004).…”
Section: Prophylaxis a Cochrane Systematic Review Included 16mentioning
confidence: 95%
See 3 more Smart Citations
“…Thus, the results indicate that, in this study, echinacea was no more effective than placebo in preventing rhinovirus infection. However, it is possible that the study did not have sufficient statistical power to detect a difference between the two groups (Sperber et al 2004).…”
Section: Prophylaxis a Cochrane Systematic Review Included 16mentioning
confidence: 95%
“…Several new trials of echinacea preparations in the prevention of the common cold have been completed since the Cochrane review, but most have not shown beneficial effects for echinacea preparations compared with placebo on main outcome measures (Melchart et al 1998;Grimm & Mu¨ller 1999;Turner et al 2000;Cohen et al 2004;Sperber et al 2004).…”
Section: Prophylaxis a Cochrane Systematic Review Included 16mentioning
confidence: 99%
See 2 more Smart Citations
“…We found 8 studies exploring the use of a varied range of solid and liquid Echinacea preparations in the treatment of cough symptoms for common cold or URTI [16,41,42,43,44,45,46,47]. A total of 1,130 patients were enrolled in these studies, with an average of 141 patients per study.…”
Section: Resultsmentioning
confidence: 99%